Upaya Penanaman Karakter Cinta Tanah Air Terhadap Peserta Didik SD Negeri 100960 Aek Bayur - Dewi Nurhasanah Nasution; Agus Satria Daulay (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research is motivated by the decline in student character, one of the causes of which is the education system which is considered to prioritize knowledge and ignores character values ​​which must be instilled from an early age by students in line with the development of increasingly modern times, namely 4.0. This research uses a descriptive qualitative approach which aims to determine efforts to instill the character of love for the homeland in students as well as the role of teachers and school principals in instilling the value of the character of love for the homeland in students. The research subjects were students, teachers and school principals. The research methods are observation, interviews and documentation. The results of the research show that there is implementation of the character values ​​of love for the country in students at SD Negeri 100960 Aek Bayur according to the indicators of love for the country and being proud of being Indonesian, respecting differences, prioritizing the public interest and appreciating the services of heroes. The results of the research also show that in instilling the character value of love for one's country in students at SD Negeri 100960 Aek Bayur there are obstacles in its implementation.